The Effect of Emotional Intelligence and Learning Interest on Accounting Understanding Among Students - I Gede Giri Putra Wijaya; I Gusti Ayu Made Asri Dwija Putri (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2025)
Accounting understanding is one of the essential competencies that accounting students must possess to support both academic and professional success. However, this level of understanding is not only affected by cognitive factors but also by non-cognitive factors such as emotional intelligence and learning interest toward the level of accounting understanding among students. This research employs a quantitative approach with a survey method involving students of the 2022 cohort from the undergraduate accounting study program, Faculty of Economics and Business, Udayana University. The population in this study consists of 2022 cohort students of the undergraduate accounting study program at Udayana University. The sample was determined using a random sampling method, and the total population was processed using the Slovin formula, resulting in 100 samples. Data analysis was conducted using SPSS. The results of this study indicate that emotional intelligence and learning interest have a positive effect on the level of accounting understanding. These findings provide empirical insights into the main factors that affect the level of accounting understanding among students.